Analysis of water vapor adsorption in soils by means of a lysimeter and numerical modeling - Saaltink, M.W. (2020)
The analysis shows that daily temperature oscillations, psychrometrics, and soil water retention can explain the fluctuations of the amount of liquid water in the soil. The retention curve, especially its driest part, is essential for the existence of these fluctuations. The fluctuations could not be reproduced by a model using the van Genuchten retention curve with a constant residual saturation. On the other hand, satisfactory results could be obtained by models using retention curves that at their driest part still show a change of saturation with suction. Moreover, the models suggest within the top few decimeters of the soil a pattern of alternating bands of condensation and evaporation, which follows the daily temperature oscillations that fade out deeper in the soil.